EXPERIENCE OF THE EXTRACORPOREAL SHOCK-WAVE LITHOTRIPSY (ESWL) TREATMENT IN OUR DEPARTMENT OF UROLOGY - OKA, Toshitsugu; TAKAHA, Minato; TSUJIMURA, Akira; SUGAO, Hideki; IMAZU, Tetsuo; NISHIMURA, Kenji (Japanese Journal of National Medical Services, 1993)
Experience of extracorporeal shock wave lithotripsy (ESWL) using the MPL 9000 lithotriptor at the Department of Urology of Osaka National Hospital is reported. The MPL 9000 lithotriptor are characterized by having both ultrasound and fluoroscopic imaging for accurate stone localization and real-time treatment monitoring. Between May 12 and December 31, 1992, 58 patients underwent 126 treatments for 65 stones, which were located in the renal calyx and/or renal pelvis including 3 cases of staghorn calculus (37 cases), pelvicoureteral juncture (PUJ) (2 cases), upper ureter (15 cases), middle ureter (3 cases), lower ureter (1 case), bladder (2 cases) and others (4 cases). Out of the 65 stones in 58 patients, 58 stones in 52 patients and 38 stones in 36 patients were available with follow-up≥one-month and≥three-month, respectively. The overall stone-free rate one-month and three-month after the last ESWL treatment were 48.3% and 68.4%, respectively. The operative auxiliary procedures after ESWL were required in 2 patients, one was transurethral ureterolithotripsy (TUL) for the patient with left lower ureteral stone and the other was percutaneous nrphrolithotripsy (PNL) for the patient with left staghorn calculus. Although we experienced five cases in 4 patients (8.6%) of perirenal hematoma, all of them required no blood transfusion. We believe that our experience of ESWL with the MPL 9000 lithotriptor demonstrated an almost favorable result.